TAMUNGGU DOLO PENYELAMAT BUDAYA PAHLAWAN PERDAMAIAN SEBUAH SANGGAR SENI - Fadli, Muhammad Rajab; Saganta, Ira Juwita; Kullin, Kristina (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
The lost No Siala Pale culture cause conflict epidemic which spread in Sigi Regency. Therefore, a method to bring yearn peacefulness back is needed. The most effective method are drama performance and empowerment of art community. Through drama performance, No Siala Pale is able to cultivated again. In the other side, conflict is able to muted with empowerment of art community. It is evidenced by reducing frequency of conflict in Kotarindau Village from 20 in 2013 to 2 in 2014. Kotarindau community that was once accustomed to art, now back to preserve the culture and keep the peace. It can only be achieved after the Art Community Tamunggu Dolo empowered again. Thus, we recognize that Tamunggu Dolo is a cultural savior and hero of peace. Keywords: conflict, culture, No Siala Pale, drama, Art Community.